Sosialisasi Alat Peraga IPA Perpindahan Kalor di SDN Kedai Runding, Kec. Kluet Selatan, Kab. Aceh Selatan - Faizin Faizin; Patri Janson Silaban; Lasma Silaban (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
This dedication was motivated by a problem among the students of SDN Kedai Runding, namely that some students had difficulty in understanding the concept of science and the learning outcomes were still low. This happens because teachers only use lectures, questions and answers and assignments in learning, not moving students' enthusiasm to actively participate in learning. To overcome this, Apperpa is used in learning, because by using Apperpa students can be actively involved directly and discover for themselves the concept of science so as to help students who have learning difficulties. The approach or method that I use in this socialization, namely Participatory Action Researc (PAR) is a research approach that involves active participation of community groups that are the subject of research, this method aims to produce knowledge that is relevant, useful, and can be applied in everyday life. This activity was carried out at SDN Kedai Runding in Class V. With the Apperpa Science Props which contains experiments on heat transfer, students can easily understand the concept of heat transfer using teaching aids.